2021
DOI: 10.2215/cjn.09140620
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in Deceased-Donor Kidney Transplant Access by Cause of Kidney Disease

Abstract: Background and objectivesWomen with kidney failure have lower access to kidney transplantation compared with men, but the magnitude of this disparity may not be uniform across all kidney diseases. We hypothesized that the attributed cause of kidney failure may modify the magnitude of the disparities in transplant access by sex.Design, setting, participants, & measurementsWe performed a retrospective cohort study of adults who developed kidney failure between 2005 and 2017 according to the United States Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Within nephrology, it is well documented that women with kidney failure have reduced access to the transplant waiting list and to deceased donor transplantation. 91 The reasons for this are complex and might reflect disparities between outcome measures discussed earlier. 10 Serum creatinine is a commonly used indicator of kidney function but is not directly comparable between the sexes.…”
Section: Accessing Information and Health Carementioning
confidence: 99%
“…Within nephrology, it is well documented that women with kidney failure have reduced access to the transplant waiting list and to deceased donor transplantation. 91 The reasons for this are complex and might reflect disparities between outcome measures discussed earlier. 10 Serum creatinine is a commonly used indicator of kidney function but is not directly comparable between the sexes.…”
Section: Accessing Information and Health Carementioning
confidence: 99%
“…found an interaction between sex and the etiology of kidney disease, where women with type 2 diabetes had a 27% lower access to the waitlist compared to men. This disparity was more pronounced for older women and was non‐existent in women with kidney failure attributed to cystic disease 28 …”
Section: Introductionmentioning
confidence: 98%
“…24 It is known that compared with males, females have reduced referral for kidney transplant, less activation on the waitlist once referred, are less likely to undergo transplant once activated [25][26][27] , have pregnancy-induced presensitization, as well as postulated attitudes that women may be perceived by care providers to be less eligible for transplant than men, even with similar or reduced comorbidity burden. 28 Potential explanations for more first and repeat PKT in females than males may include a faster rate of progression to ESKD in males 29 that precludes appropriate preparation for PKT. However, we found that males undergo PKT at a significantly higher eGFR than females do.…”
Section: Discussionmentioning
confidence: 99%